A taxonomy of blockchain technology application and adoption by small and medium-sized enterprises - Deepak Kumar Singh; B. V. Phani; Naveen Chilamkurti; Suman Saurabh; Vanessa Ratten (Entrepreneurial Business and Economics Review (EBER), 2024)
Objective: The objective of the article is to comprehensively examine the application and adoption of blockchain technology in SMEs. Recently, blockchain technology has garnered substantial attention owing to its transformative potential across diverse industries. Blockchain represents a decentralized and distributed ledger system that ensures data transparency, security, and immutability. This unique set of attributes has garnered attention from various sectors, ranging from finance and healthcare to supply chain and beyond. While predominant attention has been directed towards its impact on large corporations and financial institutions, the application and adoption of blockchain technology in small and medium-sized enterprises (SMEs) remains a relatively unexplored area. Research Design & Methods: This research utilized a narrative and critical literature review of the existing literature on blockchain technology and SMEs. Findings: We identified the key areas of application and drivers and barriers to SMEs' adoption of blockchain technology. Supply chain and finance have emerged as primary domains witnessing heightened blockchain implementation. The intricate nature of supply chain operations involving a multitude of stakeholders and the centralized nature of financing with inherent information asymmetry have propelled blockchain adoption within these sectors. However, the complex nature of technology, regulatory uncertainty, and lack of technological capabilities of SMEs have been the barriers inhibiting the widespread adoption of blockchain technology in SMEs. Implications & Recommendations: The insights derived from this study can facilitate the successful design and implementation of blockchain-based solutions for SMEs. Blockchain solution providers must understand and tailor the solutions to SMEs. Blockchain-as-a-service (BaaS) can accelerate flexible application development, expediting blockchain integration in SMEs. Government, regulatory bodies, and SME groups are urged to collaborate in enhancing technological literacy among SMEs, facilitating their capacity to harness the advantages offered by blockchain technology. Contribution & Value Added: This research contributes to the field by shedding light on the underexplored realm of blockchain technology in SMEs. The created taxonomy, examination of adoption drivers and barriers, and the formulated opportunities-challenges framework provide valuable tools for understanding and navigating blockchain technology's application and adoption-related challenges in SMEs. The identified gaps and proposed areas for future research further contribute to the ongoing discourse in this evolving field.
Keywords: O33; O35; 330; Blockchain technology; small and medium-sized enterprises (SMEs); Taxonomy; Application; adoption